수학 학습에 어려움이 있는 학생 대상 국내 분수 중재 연구의 동향 분석 - 이형식(Lee, Hyeongshik); 홍정순(Hong, Jeongsun); 박진석(Park, Jinseok) (특수교육논총, 2024)
연구목적: 본 연구는 수학에 어려움이 있는 학생을 대상으로 한 국내 분수 중재 연구의 최근 동향을 체계적으로 고찰하여 분수 중재를 위한 구체적이고 유용한 정보를 제공하고자 하였다. 연구방법: 2014년부터 2023년 사이에 수학에 어려움이 있는 학생을 대상으로 한 국내 분수 중재 연구를 수집하여 16편의 논문을 선정하였고, 이를 일반적인 연구 특성과 구체적인 중재 특성으로 분석하였다. 연구결과: 일반적인 연구 특성의 분석 결과는 다음과 같다. 첫째, 2018년에 출판된 연구와 학술지 논문이 많은 것으로 나타났다. 둘째, 초등 고학년, 1~3명, 학습지원대상학생을 연구 대상으로 선정한 연구가 많았다. 셋째, 연구 설계 방법으로 대상자 간 중다간헐기초선 설계를 많이 활용하였고, 중재 충실도 평가는 실시한 연구가 많았지만, 유지와 일반화 평가는 실시하지 않은 연구가 더 많았다. 관찰자 간 신뢰도 평가와 사회적 타당도 평가는 실시한 연구와 그렇지 않은 연구의 수가 비슷하였다. 구체적인 중재 특성의 분석 결과는 다음과 같다. 첫째, 중재 장소는 교실, 중재자는 연구자, 집단 크기는 1:1, 중재 기간은 16~20회기, 중재 시간은 회기당 31~40분인 연구가 많았다. 둘째, 중재 내용으로 분수의 의미는 측정, 중재 초점은 개념적 지식과 절차적 지식, 교육과정 내용은 분수의 이해와 분수의 크기 비교, 분수의 덧셈과 뺄셈을 지도한 연구가 많았다. 셋째, 중재 방법으로 길이 모델, 다양한 표상을 활용한 연구가 많은 것으로 나타났다. 넷째, 평가 방법으로 연구자가 개발한 평가 도구를 많이 활용한 것으로 나타났다. 결론: 연구 결과를 바탕으로 수학에 어려움이 있는 학생을 대상으로 한 분수 중재와 연구의 방향을 논의하고 제언하였다. Purpose: This study aims to provide specific and useful information for fraction intervention by systematically reviewing recent trends in domestic fraction intervention research targeting struggling learners in mathematics. Method: We collected and analyzed 16 domestic fraction intervention studies from 2014 to 2023, focusing on general study and specific intervention characteristics. Results: The results regarding general research characteristics revealed the following. First, many studies were published in 2018 and in academic journals. Second, many studies targeted upper elementary students, involved one to three participants, and selected students eligible for learning support. Third, a multiple probe across participants design was predominantly used as a research design method, with frequent intervention fidelity evaluations but fewer maintenance and generalization evaluations. Inter-observer reliability and social validity evaluations were similarly distributed between conducted and non-conducted studies. The analysis of specific intervention characteristics revealed the following. First, many studies were conducted in classroom settings, with researchers as interventionists, utilizing 1:1 group size, 16 to 20 sessions, and 31 to 40 minutes per session. Second, many studies emphasized teaching the meaning of fractions through measurement concepts. The interventions focused on both conceptual and procedural knowledge, and covered curriculum content such as understanding fractions, comparing fractions, and adding and subtracting fractions. Third, as intervention methods, many studies employed length models and various representations. Fourth, many studies adopted evaluation tools developed by researchers. Conclusion: Based on these findings, we discussed and proposed directions for fraction intervention and research for learners struggling in mathematics. KCI Citation Count: 1